Efficiency of Tannin Reduction in Stevia Extract by Coagulation with Lime and Adsorption with ion Exchange Resin - Polban, Riniati; Sudrajat Harris Abdulloh; Endang Widiastuti; Ari Marlina (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
Stevia, a plant commonly used as a natural sweetener, has the potential to be used as a sugar substitute because the stevioside content provides high sweetness and has a low caloric value. On the other hand, stevia contains tannins that can give it a bitter taste. To reduce the tannin content in stevia extract, tannin is coagulated with calcium metal ions from lime and then passed into a ion exchange resin column. The purpose of this study was to determine the effect of lime concentration on the reduction of tannin levels and the efficiency of resin columns in reducing tannin levels. However, it is expected that the extract still has a high level of sweetness. Extraction was carried out on dried stevia leaves using water solvent in a ratio of 1:30 (w/v). After coagulation with lime, the extract was filtered and then passed to the resin column to bind the remaining calcium ions. The concentration of lime was varied: 0,5; 1; 1,5; 2; 2,5; 3; 4; 5; 6 %. The tannin content in the extract, before and after the process was tested by spectrophotometric method using Folin Ciocalteu reagent. The sweetness level of the extract was tested by measuring the % brix value using a brix refractometer. The results showed that the high efficiency of significant tannin content reduction was 99.98% with a minimum sweetness level reduction of 47.1% at 2% (w/v) lime addition.